Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/cwe.12338
|View full text |Cite
|
Sign up to set email alerts
|

Flying with the Dragon: Estimating Developing Countries’ Gains from China's Imports

Abstract: As a large trading nation, China competes with importing countries’ domestic and third‐country markets but also creates growth opportunities for exporters. Most studies on China trade shocks or “China shocks” focuse on the impacts of import competition on developed economies. The present paper complements research on China shocks by exploring the other side of the trade exposure to China – China as the largest importer, rather than as an exporter. We analyze the effects of export expansion into China on the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…On the other hand, developing economies have fewer alternative export markets and greater space for improvement in productive technology and product quality, and hence the exporters in developing countries have more incentives and greater motivation to improve product quality to meet China's new standards. Qian et al (2020) showed that China, as the largest importer, creates jobs and growth opportunities in manufacturing industries for the exporting developing countries. We therefore aim to examine the specific impact of China's public policy NTMs on the intermediate imports sourced from different economies.…”
Section: Annual Survey Of Manufacturing Enterprisesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, developing economies have fewer alternative export markets and greater space for improvement in productive technology and product quality, and hence the exporters in developing countries have more incentives and greater motivation to improve product quality to meet China's new standards. Qian et al (2020) showed that China, as the largest importer, creates jobs and growth opportunities in manufacturing industries for the exporting developing countries. We therefore aim to examine the specific impact of China's public policy NTMs on the intermediate imports sourced from different economies.…”
Section: Annual Survey Of Manufacturing Enterprisesmentioning
confidence: 99%
“…improvement in productive technology and product quality, and hence the exporters in developing countries have more incentives and greater motivation to improve product quality to meet China's new standards Qian et al (2020). showed that China, as the largest importer, creates jobs and growth opportunities in manufacturing industries for ©2021 Institute of World Economics and Politics, Chinese Academy of Social Sciences the exporting developing countries.columns (1) and (2) show that both types of Chinese NTMs give rise to an additional range of import varieties of intermediates at the whole product level.…”
mentioning
confidence: 99%